INVESTASI ILEGAL BERKEDOK ROBOT TRADING MENURUT HUKUM PIDANA DI INDONESIA - Farosi, Mohamamd; Nugroho, Widhi Cahyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
In this modern era, there have been many developments in human life both in the economic and technological fields. In the economic field one of the developments that can be seen is a form of investment. Investment today can be done using technology. As for stocks, forex and crypto where you can implemented in a practical manner. Many people are interested in investing because it is facilitated by using software. The large public interest in investing is used as a field by criminals. The modus operandi used is by packaging modern investments with the use of trading robots. Regarding the regulations regarding investment actually contained in Law No. 25 of 2007 concerning Investment. However, the Law does not contain criminal penalties and regulations regarding fraud by using technology in investing. The true element of fraud is contained in Article 378 of the Criminal Code which, if related to illegal investment cases under the guise of robot tra ding will be found one of the elements that has not been fulfilled. So it can be concluded that regulations regarding investment activities using trading robots in Indonesia have not been regulated explicitly. Meanwhile, regulations for the use of technology are regulated in Law Number 19 of 2016 Amendment to Law Number 11 of 2008 concerning Information and Electronics. The law also does not contain regulations regarding investment using technology, only regulations regarding electronic transactions. has not been explicitly regulated, researchers will discuss and analyze criminal acts in this case. in Indonesia